2006
DOI: 10.1002/app.25377
|View full text |Cite
|
Sign up to set email alerts
|

Multiwall‐carbon‐nanotube‐reinforced poly(ethylene terephthalate) nanocomposites by melt compounding

Abstract: Poly(ethylene terephthalate) (PET) nanocomposites reinforced with multiwall carbon nanotubes (MWCNTs) were prepared through melt compounding in a twin-screw extruder. The presence of MWCNTs, which acted as good nucleating agents, enhanced the crystallization of PET through heterogeneous nucleation. The incorporation of a small quantity of MWCNTs improved the thermal stability of the PET/MWCNT nanocomposites. The mechanical properties of the PET/MWCNT nanocomposites increased with even a small quantity of MWCNT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(51 citation statements)
references
References 18 publications
6
45
0
Order By: Relevance
“…These improvements were followed by a slight drop in r u at 0.6 and 0.8 wt% of MWCNT loading. A similar study conducted by Kim et al [32] investigated the effect of A-MWCNTs loading on the mechanical properties of a PET matrix. The authors reported that 10 % enhancement for both r u and E at 0.5 wt% CNTs.…”
Section: Tensile Resultsmentioning
confidence: 92%
“…These improvements were followed by a slight drop in r u at 0.6 and 0.8 wt% of MWCNT loading. A similar study conducted by Kim et al [32] investigated the effect of A-MWCNTs loading on the mechanical properties of a PET matrix. The authors reported that 10 % enhancement for both r u and E at 0.5 wt% CNTs.…”
Section: Tensile Resultsmentioning
confidence: 92%
“…uniaxial deformation, injection moulding, melt spun fibres and shear flow) [12,[29][30][31][32][33][34][35][36]. In these studies, the MWCNTs are aligned with the polymer chains during processing (under shear flow), and so oriented NHSK morphologies are seen, where again the MWCNTs act as oriented nucleation sites for epitaxial crystallization.…”
Section: Introductionmentioning
confidence: 75%
“…The morphology of the MWCNTs oxidized by a sequential treatment based on diluted HNO 3 followed by H 2 O 2 (treatment B, Figure 4b) is similar to that of the as-received MWCNTs, indicating that structural damage is either absent or small. For the MWCNTs oxidized by the concentrated mixture of HNO 3 and H 2 SO 4 (treatment C), the CNTs exhibit severe structural damage, as shown in Figure 4c. This concentrated mixture of acids causes conversion of the original graphitic structure to amorphous carbon with the consequent increase in CNT roughness and waviness as observed in Figure 4c.…”
Section: Transmission Electron Microscopymentioning
confidence: 99%